English Imperialism: A Structural Form of Colonialism in the Intercultural Communication - Win Listyaningrum Arifin (UIN Salatiga, 2023)
This study aimed to investigate the intercultural communication life of six Indonesian PhD Muslim female students in Australia as transnationals during their first year living caused by English imperialism. English plays an essential role as the first place of language hierarchy in the global connection. Adopting the linguistic imperialism of Phillipson and the identity negotiation theory of Stella Ting-Toomey, this ethnography study tries to uncover questions on challenges in intercultural communication caused by English imperialism: (1) How far is English as linguistic imperialism to their mutual intercultural communication? Moreover, (2) To what extent does linguistic imperialism influence intercultural communication competence? This study is a qualitative approach using autoethnography and interview techniques to obtain data of the self-experience of Indonesian Muslim female doctoral students in Australia. Later, these female students own their 'mindful' knowledge, motivation, and skill to obtain their adaptive, effective, and appropriate strategy in supporting their identity construction's successfulness under the superiority of English.